(untitled) (Research, Society and Development, 2021)
As in the rest of the world, Brazil faced a rapid advance of contamination by covid-19 and in June 2021, more than 16 million Brazilians had already been infected and deaths were approximately 500 thousand. Among the most affected groups were people over 60 years of age, especially those who had some type of comorbidity. Due to the rapid evolution and worsening of patients in this age group, nurses must adopt measures that contribute to the improvement of this patient, as well as measures to prevent the spread of the virus. In this context, the aim of this study was to describe the clinical practice of nurses in the health care of elderly people with covid-19. The methodology was a bibliographic review with a descriptive and qualitative approach of studies published in 2020 and 2021. Given the complexity of the human aging process, with its own peculiarities, combined with the high incidence of chronic diseases and their repercussions on the human body, and the need for specific attention to the elderly, which includes prevention, treatment, and rehabilitation actions. Regarding the elderly with covid-19, it is worth emphasizing the importance of fast and efficient care, which guarantees the distance between the elderly affected by the disease from other people, but still providing humanized care. New scientific studies are needed to improve the clinical practice of nurses in combating the new coronavirus in the elderly, with a focus on improving the quality of life and rehabilitation for those recovered.